LifeIsADangerousGame
  • LifeIsADangerousGame
This is the question: First, solve the equation for y. (5 points) Second, find the value of y for the given x-value. (5 points) 3x - 2y = -7, when x = 3 This is my answer: Is it correct? 1. 3x - 2y = -7 3x - 2y - 3x = -7 - 3x -2y = -3x + 7 -2y/-2 = -3x + 7/2 y = -3/2x + 7/2 2. 3x - 2y = -7 3 X 3 - 2y = -7 9 - 2y = -7 9 - 2y - 9 = -7 - 9 -2y = -16 y = 8
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Check the second one...why are you multiplying 3 with 3x?
LifeIsADangerousGame
  • LifeIsADangerousGame
Because she(my teacher) wants to know what y is and she told me that x is 3
LifeIsADangerousGame
  • LifeIsADangerousGame
In the second one, I'm not solving it as a slope equation, but as a regular "find x or y" equation

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Hero
  • Hero
Technically, yes, but, I believe it was meant to be solve in a certain way. Check out my solution: 1. 3x - 2y = -7 3x - 2y - 3x = -7 - 3x -2y = -3x - 7 -2y/-2 = 3x + 7/2 y = 3/2x + 7/2 y = (3x + 7)/2 2. y = (3x + 7)/2 y = (3(3)+7)/2 y = (9+7)/2 y = (16)/2 y = 8
Hero
  • Hero
By the way, you also made some algebraic mistakes in the first part. I corrected them for you.
LifeIsADangerousGame
  • LifeIsADangerousGame
Ohhh thanks!

Looking for something else?

Not the answer you are looking for? Search for more explanations.